Ocular hypertension and its predictor after a single Ozurdex implant: One-year follow-up in Asian Indian eyes - Tarannum Mansoori; Swathi Shiva; Nagalla Balakrishna (Oman Journal of Ophthalmology, 2022)
BACKGROUND: To determine the incidence and risk factors for an increase in the intraocular pressure (IOP) after a single dexamethasone intravitreal implant (Ozurdex). MATERIALS AND METHODS: Medical records of 41 consecutive eyes who had received a single 0.7 mg Ozurdex implant for the various vitreoretinal pathology, between March 2015 and April 2016 were reviewed retrospectively. Ocular hypertension (OHT) was defined as IOP of >22 mmHg or an increase in the IOP of >6 mmHg from the baseline. Univariate regression analysis was used to measure the predictor of OHT after the implant. RESULTS: Among the 41 eyes, who received a single Ozurdex intravitreal implant, 6/41 (14.6%) of the injected eyes had OHT, with the peak of IOP at 1 month after the injection when compared with the baseline IOP. Eight eyes (19.5%) had preexisting glaucoma or OHT, and 4/8 (50%) of them developed sustained elevation of IOP after the injection. Two eyes had transient OHT, a day after the implant, which did not require any treatment. All the eyes were managed with topical antiglaucoma medications and none required surgery to control the IOP. Preexisting OHT or glaucoma was found to be a significant risk factor for OHT after the Ozurdex injection (P < 0.0001). CONCLUSION: Patients with preexisting OHT or glaucoma have an increased risk of OHT following the Ozurdex implant and hence needs to be informed of the possible risk. Follow-up at a regular interval is mandatory to monitor and recognize OHT early and treat it appropriately.